Slab to back-arc to arc: fluid and melt pathways through the mantle wedge beneath the Lesser Antilles - Hicks, SP; Bie, L; Rychert, CA; Harmon, N; Goes, S; Rietbrock, A; Wei, SS; Collier, JS; Henstock, TJ; Lynch, L; Prytulak, J; Macpherson, CG; et al. (American Association for the Advancement of Science, 2023)
Volatiles expelled from subducted plates promote melting of the overlying warm mantle, feeding arc volcanism. However, debates continue over the factors controlling melt generation and transport, and how these determine the placement of volcanoes. To broaden our synoptic view of these fundamental mantle wedge processes, we image seismic attenuation beneath the Lesser Antilles arc, an end-member system that slowly subducts old, tectonized lithosphere. Punctuated anomalies with high ratios of bulk-to-shear attenuation (Qκ−1/Qμ−1 > 0.6) and VP/VS (>1.83) lie 40 km above the slab, representing expelled fluids that are retained in a cold boundary layer, transporting fluids toward the back-arc. The strongest attenuation (1000/QS ~ 20), characterizing melt in warm mantle, lies beneath the back-arc, revealing how back-arc mantle feeds arc volcanoes. Melt ponds under the upper plate and percolates toward the arc along structures from earlier back-arc spreading, demonstrating how slab dehydration, upper-plate properties, past tectonics, and resulting melt pathways collectively condition volcanism.